GAMING DISORDER DAN MOTIVASI BELAJAR PADA KESEHATAN MENTAL REMAJA - Wetik, Syenshie V; Sepang, Mareyke; Worotikan, Roxane (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
ABSTRACT Introduction: Since the Covid-19 pandemic, access to online games has increased and this has become an activity that is considered common for society, especially for teenagers. Seeing the various phenomena that occur because of excessive use of online games, the World Health Organization (WHO) has made Gaming Disorder a mental illness in the Diagnostic and Statistical Manual of Mental Disorder (DSM-5) with the characteristic of being unable to control oneself to stop playing. Playing games has even become part of life's needs and routine. The high duration of playing online games has a negative and positive impact on teenagers' learning motivation. This then affects the mental health of teenagers. Objective: The aim of this research is to identify the picture of gaming disorder and learning motivation on the mental health of teenagers in Taas Village, Manado City. Method: This research is quantitative with a descriptive analysis design. The population is late teenagers (18-22 years) = 205 teenagers with a sampling technique, namely purposive sampling so that the number of respondents is 90 teenagers. The research instrument used the Indonesian Online Game Questionnaire (IOGQ) questionnaire and data analysis used univariate analysis. Results: the description of gaming disorder showed that 71.1% were in the mild category and 60% of teenagers' learning motivation was in the high category. Conclusion: related to the mental health of teenagers in Taas Village, most teenagers are in the mild category of gaming disorder with learning motivation in the high category.